Historical review of the Indonesian government's response to health crisis: from the Spanish flu to the COVID-19 pandemic - Miftah, Ahmad Zaini; Widianingsih, Ida; Hoe, Connie; Afriandi, Irvan (One health, 2025)
In the current post-pandemic era, One Health has emerged as an important notion, integrating concern for human, animal, and environmental health in addressing the threat of communicable disease. Communicable diseases are not a new phenomenon, as evidenced by the Spanish Flu, the Asian Flu Pandemic, Swine Flu, Bird Flu, SARS, MERS, and others. However, Indonesia has not been able to respond to the Covid-19 pandemic quickly. This study employs a retrospective policy analysis approach to the government's policy responses to health crises stemming in Indonesia, spanning from the Spanish flu pandemic to the COVID-19 pandemic. The results of this study found that the implementation of One Health in the management of infectious diseases needs to reform the national health system. It requires aspects of One Health that are proportionally integrated between humans, animals, and the environment. With this historical approach, how the Dutch East Indies government and the Indonesian government handled the outbreak becomes a lesson for improving policies. Government needs to integrate policies between sectors to minimize policy barriers and rigid segmentations that hinder coordination, as well as proportional financial funds.
Online verfügbar: 10. Mai 2025, Artikelversion: 22. Mai 2025
Gesehen am 15.09.2025